Performance evaluation of plants raised through different propagation methods in pomegranate (Punica granatum) - SINGH, N V; PARASHURAM, SHILPA; ROOPASOWJANYA, P; BABU, K D; MUNDEWADIKAR, D M; SANGNURE, VIPUL; SHARMA, JYOTSANA; PAL, R K (The Indian Journal of Agricultural Sciences, 2020)
Disease free and elite planting material propagated through in vitro propagation may prevent the spread of diseases particularly bacterial blight through infected planting material. However, there are certain misapprehensions about fruit quality of harvest from micro-propagated plants as compared to air layered or hardwood cutting raised plants. Keeping these facts under consideration, an elaborate study on comparative qualitative and quantitative evaluation of harvest from different types of planting material had been carried out during 2015-17 at ICAR-NRC on Pomegranate, Solapur. The terminal bearing non-significantly ranged from 25 to 28.30% across the different types of planting material. Fruit weight and aril to fruit ratio were found at par in harvest from the three types of planting material. Rind thickness and PLW, which generally play critical role in governing fruit shelf life, were also found at par in fruits from all the three types of planting materials. The rind to fruit ratio of fruits from hardwood cutting raised plants (0.41) was found significantly higher than air layered plants. The maximum ‘L*’ and ‘b*’ values of fresh fruits were recorded for fruits from air layered plants (60.76 and 31.65, respectively) and ‘a*’ value for fruits from TC raised plants (39.70). The results proved parity among fruit quality of harvests from different types of planting material in pomegranate (Punica granatum L.) cv. Bhagwa.